2014
DOI: 10.1021/je400595k
|View full text |Cite
|
Sign up to set email alerts
|

Phase Behavior of Vegetable Oil-Based Ionic Liquid Microemulsions

Abstract: This study presents the formation and phase behavior of vegetable oil-based ionic liquid microemulsions (ILMs). Castor oil, jatropha oil, and soybean oil were used as oil phases of the ILMs respectively. The effects of the mass ratio of surfactant to cosurfactant (K m ) and temperature on the phase behavior of ILMs were investigated by pseudo ternary phase diagrams. The results indicated that the homogeneous and stable microemulsions composed of target vegetable oils, ionic liquid, Triton X-100, and n-butanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…The results obtained by Djekic et al [ 11 ] suggested that dilutable olive oil microemulsions could only be formed at a surfactant-to-cosurfactant mass ratio of 1:9, whereas a medium-chain triglyceride was easier to disperse as a microemulsion. In addition, a recent publication successfully developed a dilutable microemulsion composed of soybean oil, ionic liquid, TX-100, and n-butanol [ 12 ]. Although some dilutable triglyceride microemulsions have been prepared as described above, their applications in food are still limited to non-food grade surfactants or co-surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained by Djekic et al [ 11 ] suggested that dilutable olive oil microemulsions could only be formed at a surfactant-to-cosurfactant mass ratio of 1:9, whereas a medium-chain triglyceride was easier to disperse as a microemulsion. In addition, a recent publication successfully developed a dilutable microemulsion composed of soybean oil, ionic liquid, TX-100, and n-butanol [ 12 ]. Although some dilutable triglyceride microemulsions have been prepared as described above, their applications in food are still limited to non-food grade surfactants or co-surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 23 It has been reported that the phase-forming capacity of a traditional water−oil microemulsion depended on the packing symmetry between the surfactant and water−oil phases. 28 9 Our previous work showed that after altering a quarter of TX-100 by [C 8 mim][Cl] in castor oil-based ionic liquid microemulsions, the driving force of constructing microemulsions would be enhanced and the S ME in the pseudoternary phase diagram would be enlarged.…”
Section: [Bmim][tf 2 N]-based Microemulsion > [Bmim][pf 6 ]-Based Micmentioning
confidence: 99%
“…23 For castor oil-based systems, the microemulsion region areas increased with the increase of temperature and K m . In this paper, we further explored the effects of ionic liquid anions and cations, surfactant types, and cosurfactant chain length on the phase behavior of castor oil-based ionic liquid microemulsions.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…[9][10][11][12] Our previous study also indicated that vegetable oil-based ionic liquid microemulsions may have potential as biolubricant basestocks, and the phase behavior of ionic liquid-in vegetable oil microemulsions were further detailed in recent studies. [13][14][15] In order to response to the requirements of lubrication efficiency positively, the development and application of additives, particular at the nanoscale, have made a rapid growth over the past few years, because lubricants with nanoparticles as additives (hereaer referred to as "nanolubricants") can offer excellent anti-wear and friction-reducing properties. [16][17][18][19][20] Numerous nanoparticles, particularly Cu, have been investigated as component of nanolubricants.…”
Section: Introductionmentioning
confidence: 99%